Problem Finding dalam Pembelajaran Pendidikan Agama Islam Di Era Digital - Muhammad Gafarurrozi (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
The purpose of this research is to find problems in PAI learning in the digital era. In the digital era, there has been a shift where the learning process uses technology based on an internet connection. The change in the direct face-to-face learning process in the classroom to connection-based learning that is connected to students only by digital technology, this creates problems for both teachers and students. In this study, the researchers tried to find problems in learning using PAI in the digital era with the library research method, namely conducting a search on the relevant previous literature to answer these problems and descriptively. The results of the study indicate that the problems found in PAI learning in the digital era are first, teachers still do not master technology well so that training is needed so that teachers are able to create learning media that attract students' interest. Second, the signal is constrained that makes students lazy to take lessons. Third, not all students have personal cellphones due to the economic limitations of their parents. Fourth, difficulty in interacting.